The origin of spin current in YIG/nonmagnetic metal multilayers at ferromagnetic resonance - 康韵 钟海 郝润润 胡树军 康仕寿 刘国磊 张引 王向荣 颜世申 吴勇 于淑云 韩广兵 姜勇 梅良模 (Chinese physics B, 2017)
Spin pumping in yttrium-iron-garnet（YIG）/nonmagnetic-metal（NM） layer systems under ferromagnetic resonance（FMR） conditions is a popular method of generating spin current in the NM layer.A good understanding of the spin current source is essential in extracting spin Hall angle of the NM and in potential spintronics applications.It is widely believed that spin current is pumped from precessing YIG magnetization into NM layer.Here,by combining microwave absorption and DC-voltage measurements on thin YIG/Pt and YIG/NM_1/NM_2（NM_1 =Cu or Al,NM_2 =Pt or Ta）,we unambiguously showed that spin current in NM,instead of from the precessing YIG magnetization,came from the magnetized NM surface（in contact with thin YIG）,either due to the magnetic proximity effect（MPE） or from the inevitable diffused Fe ions from YIG to NM.This conclusion is reached through analyzing the FMR microwave absorption peaks with the DC-voltage peak from the inverse spin Hall effect（ISHE）.The voltage signal is attributed to the magnetized NM surface,hardly observed in the conventional FMR experiments,and was greatly amplified when the electrical detection circuit was switched on.